Work Stress in Employees of the Gowa Regency Transportation Office - Muh. Darwis; Andi Nur Wulandari; Sitti Hardiyanti Arhas (Asha Publishing, 2025)
Work stress is an imbalance between the demands and resources owned by individuals; the higher the gap, the higher the stress experienced by individuals. With that, the purpose of this research is to be achieved to find out the factors that cause work stress in employees of the Gowa Regency Transportation Office. This study explores the factors causing work stress among employees at the Gowa Regency Transportation Office. This research is qualitative; therefore, to achieve the research objectives, data collection techniques are used, namely observation, interviews and documentation. There are 5 informants, namely the head of planning, reporting and finance, the head of public and special transportation, the traffic engineering management coordinator, the personnel manager, and the head of the operational supervision and control section. Based on the results of this study, it shows that work stress in employees of the Gowa Regency Transportation Office arises because employees are unable to complete their work according to the target, employees lack satisfaction, employees feel less focused in receiving directions or orders, employees lack enthusiasm at work, and there are employees who delay or are lazy at work. Work stress causes employees to experience excessive headaches, sleep disturbances (insomnia), emotional sensitivity, pessimism, and feeling overwhelmed with work; they can lose interest in work and experience a decrease in work performance. The study recommends organizational interventions such as workload adjustment, structured rest periods, effective communication, and employee support programmes to mitigate stress and improve performance.